A model of continuous improvement programme management. Issue 5 (4th April 2018) - Butler, Michael; Szwejczewski, Marek; Sweeney, Michael
Abstract: The aim of this study is to identify key management decisions that enable the sustainment of a continuous improvement (CI) initiative. To accomplish this aim, we examine the procedures and practices used by two manufacturing companies for the management of their CI initiatives; one that is successfully sustaining the effectiveness of its CI initiative and another failing to do the same. This research makes two contributions to the conceptual understanding of CI programme management. First, we identify five CI programme management factors that enable the sustainment of a CI initiative. Second, the five factors are incorporated into a new CI programme management model. The model details a 'bottom-up' procedure for the generation of manufacturing performance improvement ideas and the management of their implementation.